2009
DOI: 10.1017/s0033822200055831
|View full text |Cite
|
Sign up to set email alerts
|

Dating Charred Soil Organic Matter: Comparison of Radiocarbon Ages from Macrocharcoals and Chemically Separated Charcoal Carbon

Abstract: ABSTRACT. Radiocarbon dating of charcoal in soils is commonly used to reconstruct past environmental processes. Also microcharcoal that is chemically isolated from soil organic matter by high-energy UV photo-oxidation can be dated with 14 C accelerator mass spectrometry (AMS). We compared the 14 C AMS ages of 13 pairs of hand-picked macrocharcoals and microcharcoal samples separated via the UV oxidation method; both charcoal fractions were taken from the same soil samples (prehistoric pit fillings). We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…About one-third of the soil organic matter in pit fillings and soil horizons consisted of charred organic matter, or black carbon. AMS 14 C data of charred organic matter from soil samples selected for this study (Table 1) indicated the occurrence of fires during Mesolithic to Neolithic periods (Gerlach et al, 2006;Eckmeier et al, 2009). The control samples were taken from the soil material (Bt-horizon of Luvisols) directly next to the pits from an identical soil depth.…”
Section: Methodsmentioning
confidence: 99%
“…About one-third of the soil organic matter in pit fillings and soil horizons consisted of charred organic matter, or black carbon. AMS 14 C data of charred organic matter from soil samples selected for this study (Table 1) indicated the occurrence of fires during Mesolithic to Neolithic periods (Gerlach et al, 2006;Eckmeier et al, 2009). The control samples were taken from the soil material (Bt-horizon of Luvisols) directly next to the pits from an identical soil depth.…”
Section: Methodsmentioning
confidence: 99%
“…Our results are consistent with the hypothesis of Nocentini et al (2010) that the least stable CharC particles are the finest. However, CharC stability has also been proposed to increase with decreasing particle-size (Eckmeier et al, 2009).…”
Section: Stability Of Soc and Charcmentioning
confidence: 99%
“…If this is the case, the apparent contradictions indicated by studies reporting both fast and slow cycling charcoal may be resolved: at the soil surface charcoal is less stable, but in subsoils it can persist for millennia. Alternatively, charcoal stability has been linked with particle‐size and both coarse charcoal (Eckmeier et al , ) and fine charcoal (Nocentini et al , ) have been hypothesized as being the least stable fraction. Therefore, understanding the distribution and stability of charcoal in soils can provide the key to deciphering the black carbon cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of these molecules is heterogenous and can be represented as a "continuum" of compounds ranging from slightly charred biomass to highly condensed aromatic materials (Masiello, 2004;Bird et al, 2015), all of which are characterized by an increase in C concentration relative to their non-pyrolyzed precursors . Although part of the PyC pool is labile, PyC ages of 100s−1000s of years, and even up to 10,000 years have been reported in the top 1 m of soil, indicating that PyC can be one of the longest-lived C pools in terrestrial ecosystems (Schmidt et al, 2002Eckmeier et al, 2009). Therefore, conversion of biomass and soil C into long-lived PyC during fires may help mitigate a proportion of fire-induced C losses.…”
Section: Introductionmentioning
confidence: 99%